The Influence of Differentiated Learning Model Based on STIFIn Test on Fiqh Learning Outcomes - Romadhon, Ahmad; Amrullah, Abdul Malik Karim; Sholeh, Ahmad (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
In Islamic elementary education, addressing students’ diverse cognitive profiles remains a significant challenge, particularly in subjects requiring conceptual depth such as Fiqh. Recognizing that one-size-fits-all teaching methods often fall short, this study examines the effectiveness of a differentiated learning model based on the STIFIn psychometric framework. The objective is to evaluate whether instructional strategies tailored to students’ dominant intelligences—Sensing, Thinking, Intuiting, Feeling, or Instinct—can improve Fiqh learning outcomes. Utilizing a true experimental design, the research involved two Grade 1 classes at MI Syihabuddin Malang: an experimental class applying the STIFIn-based model and a control class using conventional teaching. Data were collected through posttests and documentation, and analyzed using an independent samples t-test. Results indicated a statistically significant improvement in the experimental class (p < 0.05), demonstrating higher mean scores compared to the control group. These findings highlight the potential of psychometric-based instruction to enhance student engagement, comprehension, and achievement. The study contributes to the field of Islamic education by affirming the value of differentiated pedagogical approaches grounded in cognitive psychology.